PROSES PEMBENTUKAN KEAKRABAN ANTAR INDIVIDU DI WARKOP DINO’X - SUMARJO, SUMARJO; Machmud, Desriansyah Adeputra (Program Studi Ilmu Komunikasi FISIP UM Buton, 2024)
Familiarity becomes essential to create a harmonious atmosphere within a social group. Familiarity can be achieved through several processes, such as introductions to adapt or get to know each other and to solve problems that arise together. The process of achieving familiarity can also occur through interpersonal communication. This qualitative method used a qualitative descriptive approach. This study found that, based on social penetration theory, the process of forming familiarity in Dino’x coffee shops could occur through four stage, namely: orientation, affective exploratory exchange, affective exchange, and stable exchange. However, individuals tend to achieve familiarity according to their own behavior, although this research was limited to our aspects in social penetration theory. Key Words: Social Penetration Theory, Interpersonal Communication, Qualitative Descriptive